The evaluation of the impact of flexion and extension angles and lateral torso flexion on the selected spine and pelvis parameters - Mirosław Mrozkowiak (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2021)
The aim of the research was to assess the impact of flexion and extension angles and lateral torso flexion on the selected spine and pelvis parameters among the population of children aged between 7 and 15 years. Material and methods. The research was conducted in randomly selected kindergartens and schools in the Warmia and Masuria region and the Pomerania region during six semi-annual editions. The study population consisted of 2,361 children. This allowed to record 16,608 observations of 31 parameters describing body posture using the photogrammetric method. Results. The analysis of multiple regression with selection of the subset of the optimal set of variables included four parameters affecting the following: flexion angle and extension angle in the sagittal plane, angle of flexion to the left and to the right in the frontal plane. The set of variables included the parameters of the pelvis-spine complex. Conclusions 1.Spinal parameters are significantly and positively affected by the angle of torso extension in the sagittal plane and the angle of flexion to the left in the frontal plane and negatively influenced by the flexion angle in the sagittal plane. 2.The values of torso extension and flexion angles in the sagittal plane and torso flexion to the left and right in the frontal plane have a significant and positive impact on the total length of the spine (C7-S1) and the percentage of growth (DCK%), the Delta angle and the height of lumbar lordosis. The inclination angle of the lumbosacral spine, the total spinal length and the percentage of body height and the height of lumbar lordosis account for the parameters that are most dependent on the angles describing vertical orientation of the axial organ. 3.The significant negative impact on the spine parameters is remarkably lower. The most negatively dependent parameters include: lumbosacral inclination angle, the length and angle of thoracic kyphosis, and lumbar lordosis angle. 4.Hardly any influence of the analysed angles on pelvis parameters demonstrated herein requires further studies on the impact of foot parameters on the parameters of pelvis and spine. 5.The significant correlations of flexion and extension angles in the sagittal plane as well as the flexion angle in the frontal plane should be taken into consideration in the process of correcting body posture defects and errors.